HALAL SUPPLY CHAIN MANAGEMENT INDUSTRI PARIWISATA - Yanti, Nursantri (Studia Economica : Jurnal Ekonomi Islam, 2023)
The tourism sector has an important role as a source of foreign exchange earnings, and can encourage national economic growth, especially in reducing the number of unemployed and increasing the productivity of a country. Muslim spending on tourism increased from US$58 billion to US$102 billion in 2021 and is expected to grow by 50.0% in 2022 to US$154 billion and reach US$189 billion in 2025. As a country with the largest number of Muslims in the world, Indonesia has good opportunities and potential to become the largest Muslim-friendly tourism destination in the world. And one of the efforts to make this happen is to understand the concept of halal supply chain management so that all the tourism sectors involved are able to offer services that comply with sharia principles. This paper will discuss the concept of halal supply chain management for the tourism industry so that it can understand the indicators of halal tourism